Алиби с того света - Леонов Николай Иванович (Русский бестселлер, 2015)
Экземпляры: п/ф (20180201) / Инвентарный номер: 51701 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: Л 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)